Alveolar Soft-Part Sarcoma of the Tongue. (March 2019) - Alegría-Landa, Victoria; Lora, Viviana; Cota, Carlo; Kutzner, Heinz; Requena, Luis
Abstract : Abstract: Alveolar soft-part sarcoma is a rare neoplasm of unknown histogenesis that accounts for less than 1% of all soft-tissue sarcomas. The tumor is highly vascularized with small vascular spaces separating nests of cells, and from cytogenetic point of view, is characterized by chromosome rearrangement der(17)t(X:17)(p11:q25) that results in the ASPL-TFE3 translocation. It can occur at any age, but it is most common between 15 and 35 years of age. The prognosis is poor, despite the relatively slow growth of the tumor. We present here an atypical case of alveolar soft-part sarcoma in which the age of the patient, the location, and the histopathologic characteristics of the lesion represented a diagnostic challenge.